Investigating the Mobile Phones Radiofrequency Waves’ Impact on Different Cows Brain Tissue Depth and Brain Tissue Temperature Variation - Hossein Ebrahimi; Siamak Pourabdian; Farhad Forouharmajd (International Journal of Occupational Hygiene, 2019)
Prevalent use of mobile phones has led to increasing worries about the effect of radiofrequency waves on the physiology of human body. This study was aimed to determine the mobile phones radiofrequency waves’ impact on different brain tissue depth and brain tissue temperature. In this empirical research, a cow’s brain tissue was placed in a compartment and the effects of radiofrequency waves of the mobile phone were analyzed during and after radiation, in three different brain tissue depths of 2, 12, and 22 mm, in 4 mm and 4 cm distances of the tissue to a mobile phone, for 15 min. Lutron thermometer was used to measure the tissue temperatures. Data were analyzed using Lutron software. The rate of temperature increasing in 22 mm depth was higher than 2 and 12mm depths. The results also showed that during radiation of the brain tissue in 4 mm distance by the mobile phone, the tissue temperatures in 2, 12, and 22 mm depths were increased 0.29 ˚C, 0.31 ˚C, and 0.37 ˚C, respectively, relative to the base temperature (tissue temperature before radiation). Moreover, the brain tissue temperature in 4 cm distance was more sensitive than other depths. There was also a direct relationship between brain tissue depth and tissue temperature increase after mobile phone radiofrequency waves’ radiation. The temperature in 22 mm depth increased with higher speed. Not only radiofrequency waves of mobile phones increased the tissue temperature in all depths of the brain tissue, but also the higher temperature was observed in the 22 mm tissue depth. In fact, the radiofrequency wave’s thermal affect was higher in higher depths.